2013
DOI: 10.1111/and.12169
|View full text |Cite
|
Sign up to set email alerts
|

In vitroeffects of nicotine on human spermatozoa

Abstract: Washed human spermatozoa from 12 normozoospermic donors were treated with different concentrations of nicotine 0.1, 1.0, 5.0 and 10.0 mm and were compared to spermatozoa suspended in nutrient medium only (control). Computer-aided sperm analysis was used to assess sperm kinematic properties after 30, 60, 120 and 180 min of incubation. Viability was assessed by means of a dye exclusion staining technique (eosin/nigrosin), while acrosome-reacted cells were identified under a fluorescent microscope using fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…was the decrease in motility parameters (Reddy et al, 1995;Condorelli et al, 2013;Oyeyipo et al, 2014). However, increase in the occurrence of late apoptotic spermatozoa with altered chromatin compactness or DNA fragmentation (Condorelli et al, 2013), reduced sperm viability (Condorelli et al, 2013;Oyeyipo et al, 2014), and premature induction of the acrosome reaction (Oyeyipo et al, 2014) have also been described in this type of experiment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…was the decrease in motility parameters (Reddy et al, 1995;Condorelli et al, 2013;Oyeyipo et al, 2014). However, increase in the occurrence of late apoptotic spermatozoa with altered chromatin compactness or DNA fragmentation (Condorelli et al, 2013), reduced sperm viability (Condorelli et al, 2013;Oyeyipo et al, 2014), and premature induction of the acrosome reaction (Oyeyipo et al, 2014) have also been described in this type of experiment.…”
Section: Discussionmentioning
confidence: 67%
“…However, increase in the occurrence of late apoptotic spermatozoa with altered chromatin compactness or DNA fragmentation (Condorelli et al, 2013), reduced sperm viability (Condorelli et al, 2013;Oyeyipo et al, 2014), and premature induction of the acrosome reaction (Oyeyipo et al, 2014) have also been described in this type of experiment. Toxicants (such as nicotine) may directly or indirectly target the DNA through oxidative stress (OS) and DNA strand breaks, which are observed in mature spermatozoa; this might injure mitotic spermatogonia or meiotic germ cells, as well as post-meiotic spermatids undergoing spermiogenesis (reviewed by Delb es et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, significant negative correlations were noticed between the degree of DNA damage and worsening of semen parameters (90). Chemicals such as nicotine (125), cadmium (126), lead (127) and benzopyrene (128) were specifically investigated and found to cause sperm DNA damage.…”
Section: Indications For Sdf Testingmentioning
confidence: 99%
“…In vitro studies have found that neither nicotine nor its metabolite cotinine in low concentrations was harmful to sperm motility (Gandini et al ., ). However, higher nicotine levels (≥1 m m ) significantly decreased sperm motion parameters and viability characteristics (Oyeyipo et al ., ). At higher concentrations, nicotine reduced the percentage of viable spermatozoa and promoted spermatozoa apoptosis, which was accompanied by DNA fragmentation or altered chromatin density.…”
Section: Introductionmentioning
confidence: 97%